Mind the gap: a warped approach to LMX agreement - Silva, Luís Filipe Dias da (2016)
Leader member exchange (LMX) has been a widely researched topic in leadership literature. Despite the amount of research done there have been few articles addressing the agreement levels of LMX perceptions. This investigation examined the influence of dispositional affect and trust as moderators of the relation between LMX agreement and Job Attitudes (i.e. job satisfaction, organizational commitment. A partial least squares structural equation model was used to analyze these moderations over a sample of 70 subordinates and leadersThe findings indicate that dispositional affect and trust do moderate the aforementioned relation in non-linear patterns, and highlight the importance of exploring LMX agreement